The sleepwalkers : a history of man's changing vision of the Universe - Koestler, Arthur, 1905-1983. (New York : Arkana, 1959)
Studies the history of cosmology from the Babylonians to Newton and explains how the split between science and religion has affected society's views of the universe.
Includes bibliographical references (p. [555]-557) and index.
Adult
Keywords: Astronomy -- History; Religion and science -- History; Astronomy -- History; Religion and science -- History